2022
DOI: 10.24310/innoeduca.2022.v8i1.11942
|View full text |Cite
|
Sign up to set email alerts
|

Influencia del aprendizaje invertido en la actitud hacia una asignatura de lengua extranjera

Abstract: Desde hace unos años viene cobrando fuerza un enfoque de aprendizaje diferente, llamado flipped learning o aprendizaje invertido. El objetivo principal de nuestro estudio es analizar, a través de una experiencia práctica en una parte de la asignatura “lengua extranjera a través de las NNTT”, la influencia de dicho enfoque en la actitud de 40 estudiantes universitarios hacia dicha materia. Para la recolección de datos se utilizaron técnicas tanto de tipo cuantitativo como cualitativo. Los resultados obtenidos r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(2 reference statements)
0
0
0
1
Order By: Relevance
“…This attitude can be due to the interactive nature of the FWQ model in teaching language. This finding is consistent with Chou et al (2021) andFernández-Carballo (2022), who state the effective role of FL in enhancing students' attitudes towards the learning process since the students who experienced the flipped classroom reported a great sense of ownership over their learning, which positively influenced their attitudes and motivation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This attitude can be due to the interactive nature of the FWQ model in teaching language. This finding is consistent with Chou et al (2021) andFernández-Carballo (2022), who state the effective role of FL in enhancing students' attitudes towards the learning process since the students who experienced the flipped classroom reported a great sense of ownership over their learning, which positively influenced their attitudes and motivation.…”
Section: Discussionsupporting
confidence: 87%
“…The findings demonstrated that combining a flipped instruction model with CLT activities effectively improved speaking skills and enhanced learning outcomes. Fernández-Carballo et al (2022) investigated the effect of FL on the attitudes of university students using ICT. The study comprised 40 university students and employed both quantitative and qualitative data collection methods.…”
Section: Flipped Learningmentioning
confidence: 99%
“…Trasladando la idea a la práctica, todo lo concerniente a la explicación de los contenidos se hace fuera del aula antes de la sesión de clase (apoyado en multitud de recursos analógicos y digitales, seleccionados o desarrollados por el docente (Guillén et al, 2020), como lecturas, vídeos, animaciones, etc. ), dejando el tiempo del aula para resolver dudas e implementar actividades de un carácter eminentemente práctico y de aplicación sobre los contenidos ya trabajados (Fernández, 2022). Con la inversión de la organización de la clase, el docente puede proporcionar una atención más personalizada al alumnado, favoreciendo tanto la mayor participación de estos en el aula (Blasco et al, 2022), como una mejora en la significatividad de sus aprendizajes.…”
Section: Introductionunclassified